A Case Study of B2C Cross-border E-commerce challenges in China — From Customs to Consumers - Yu, T. (2017)
World Customs Organization (WCO) has established a working group on E-Commerce (WGEC) in July last year. Currently, China has witnessed substantial growth in e-commerce but is still in the transitional period in terms of customs supervision mode. In light of this, the aim of this dissertation is to provide policy recommendations after addressing research questions of what are the challenges that cross-border e-commerce consumers have when importing foreign commodities into China, and what are the challenges that China Customs face when supervising these commodities. In order to address the research questions and achieve the aim, the data from Hangzhou Customs “12360” helpline center were collected, interviews with representatives from e-commerce business sectors such as Alibaba were carried out, a documentary review and analysis of international guidelines and OECD countries were conducted. By identifying and reflecting upon the challenges from both customs and consumers in the finding section, I interestingly discovered most of these problems could be addressed together and lessons could be drawn from international guidelines to make better policy recommendations. These recommendations may serve as a stepping stone for further research of shaping the new customs supervision mode for B2C cross-border e-commerce imports in China. To fill in the research gap and help consumers to understand how to import e-commerce commodities to China or for businesses to export e-commerce commodities to Chinese consumers, this study provides a review of the customs related policy development and current regulations of B2C cross-border e-commerce imports in China. The most interesting implication of the research is to consider policy recommendation from the perspective of consumers, an application of the theory of customer orientation and adoption of CRM (customer relationship management) strategy to form an e-Customs, saving time and cost of border formalities for consumers.